2017
DOI: 10.1007/s11064-017-2273-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Contributes to Status Epilepticus Associated Mortality

Abstract: Status epilepticus is a common manifestation of nerve agent toxicity and represents a serious medical emergency with high rates of mortality and neurologic injury in those that survive. The aim of the current study was to determine if targeting oxidative stress with the catalytic antioxidant, AEOL10150, would reduce pilocarpine-induced mortality and attenuate neuronal death and neuroinflammation. We found that treatment with AEOL10150 in conjunction with scopolamine and diazepam following pilocarpine-induced S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 36 publications
(45 reference statements)
2
28
0
Order By: Relevance
“…We have previously shown the efficacy of AEOL10150 against oxidative/ nitrative stress and neurodegeneration induced by chemoconvulsant agents, kainate and pilocarpine when administered at a 5 mg/kg s.c. every 4 h dosing paradigm (Liang et al, 2016;Pearson et al, 2015). This same dosing paradigm resulted in significant protection against pilocarpineinduced mortality (Pearson-Smith et al, 2017). This, in conjunction with the pharmacokinetic data detailed above lead us to determine the therapeutic window of AEOL10150 against DFP-induced oxidative stress markers.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have previously shown the efficacy of AEOL10150 against oxidative/ nitrative stress and neurodegeneration induced by chemoconvulsant agents, kainate and pilocarpine when administered at a 5 mg/kg s.c. every 4 h dosing paradigm (Liang et al, 2016;Pearson et al, 2015). This same dosing paradigm resulted in significant protection against pilocarpineinduced mortality (Pearson-Smith et al, 2017). This, in conjunction with the pharmacokinetic data detailed above lead us to determine the therapeutic window of AEOL10150 against DFP-induced oxidative stress markers.…”
Section: Discussionmentioning
confidence: 91%
“…Treatments targeting oxidative stress may therefore hold promise as novel and efficacious neuroprotective countermeasures against OP toxicity. We have previously shown that oxidative stress contributes to neuronal loss, cognitive impairment and mortality caused by the nerve agent surrogate, pilocarpine (Pearson et al, 2015;Pearson-Smith et al, 2017). However, whether an authentic OP, such as Diisopropylflurorphoshate (DFP) also results in increased indices of oxidative stress and neuroinflammation is relatively poorly understood (Flannery et al, 2016;Zaja-Milatovic et al, 2009).…”
mentioning
confidence: 99%
“…Markers of oxidative stress, such as iNOS, are modulated by chemoconvulsants, including DFP. 25,27,69,70 As fluctuating hormones and pharmacodynamic sex differences might dictate response to disease-modifying agents, we tested 1400W in female rats exposed to DFP. On the first day of treatment, 1400W suppressed seizures but not the epileptiform spikes in those females that had severe SE ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged seizure activity such as SE is associated with increased oxidative stress leading to neuronal loss and interventions aimed at attenuating seizure-induced oxidative stress have been demonstrated to be neuroprotective [6] , [7] , [8] , [9] , [10] , [11] . AEOL 10150 is a small molecular weight, superoxide dismutase (SOD) mimetic with the capability to catalytically detoxify a broad range of reactive species including superoxide, hydrogen peroxide, lipid peroxides and peroxynitrite [12] .…”
Section: Introductionmentioning
confidence: 99%